Citizen Participation in Environmental Group Events - Li, Xinru (American Journal of Human Ecology, 2015)
In recent years, Group events triggered by environmental crisis continue to occur, and there is a rising trend. Such as the PX project event in Xiamen, It has caused great hidden dangers to the safety of citizens' lives. The occurrence of these environmental group events is closely related to the degree of citizen participation. The importance of citizen participation is reflected in the solution of the mass incidents. Through these environmental group events, we can see a significant increase in awareness of citizens' participation in our country, in the meanwhile, the beginning of their own interests and aspirations. But there are some problems in the citizen participation in environmental group practice. Therefore, this paper aims to prevent and reduce the occurrence of environmental group events through the study of citizen participation in environmental group events.